Radón en la mina Coricancha, San Mateo de Huánchor - Osores y Cols., José Manuel (2019)
Radon monitoring was carried out at the Coricancha mine in order to establish a baseline on the concentration levels of this radionuclide in an underground mine in the Andean region of the country. The concentrations obtained are distributed in a wide range, from 245 to 1897 Bq/m3, with an average of 565 Bq/m3, a value that is below the limit established in the Regulation of Radiological Safety.